The Impact of Market Orientation on the Employee Performance in Health Institutions: An Exploratory Study in the Public Hospital Institution, Toubal, Mila - Boulesbaa, Mahmoud (Milev Journal of Research and Studies, 2021)
The research aims to clarify the nature of the relationship between market orientation and its impact on the employee performancein the public health institution. The study sample consisted of workers in the health institution. Among the most important findings of the study is the presence of a statistically significant effect of the relationship of market orientation, and information dissemination on the employee performance at the level of significance (α ≤ 0.05). The research did not find an effect of the dimensions of patient orientation, coordination between levels, Functional, generating information and responding to information on the employee performanceof the public hospital institution, Toobal, Mila